Selected movement and force pattern differences in rail- and rung-climbing of fire apparatus aerial ladders at 52.5° slope. (February 2022) - Fu, Qianyi Albert; Simeonov, Peter; Hsiao, Hongwei; Woolley, Charles; Armstrong, Thomas J.
Abstract: This study compares human climbing performance, including climbing speed and movement and force patterns, between rail- and rung-climbing styles for a moderate aerial ladder slope (52.5°). Hand and foot movements and forces were recorded for 9 male and 10 female firefighters as they ascended and descended a 3.4-m ladder using elevated handrails (rail-climbing) or rungs (rung-climbing) for hand support. The results indicated that climbers used three or more points of contact 54% of the time for rung-climbing and 100% of the time for rail-climbing. Furthermore, rail-climbing was 10% faster than rung-climbing. In rail-climbing, the lateral hand forces were mostly directed away from the body; while during rung-climbing, they were alternated in lateral and medial directions. Overall, the results suggested that rail-climbing provides better control over body positioning and faster climbing speed. Furthermore, the continuous contact of both hands in rail-climbing may reduce the fall risk by facilitating the recovery from a slip or perturbation. Highlights: Rail-climbing on an aerial ladder sloped at 52.5° is faster than rung-climbing. Rail-climbing provides three-point contact throughout the climbing cycle. In rail-climbing, the continuous contact of both hands may reduce the fall risk.